Shakespeare Comes to Indonesia - Skupin, Michael (Multicultural Shakespeare: Translation, Appropriation and Performance, 2013)
This paper discusses the circumstances of Shakespeare’s arrival in Indonesia via the translations of Trisno Sumardjo, published in the early 1950’s. Biographical material about the translator will be presented, and there will be a discussion of the characteristics the Indonesian language and of Indonesian verse which would determine the expectations of his readers, such as rhyme, meter and style, that would influence his renderings of the poetic passages in the Bard’s plays. These are illustrated in a sampling of passages from As You Like It, A Midsummer Night’s Dream, Macbeth and The Merchant of Venice. The Dutch translation of L. A. J. Burgersdijk was an indirect influence on the translations, and not always for the good. The paper concludes with a lengthy discussion of the extremely difficult problems that Sumardjo encountered in his translation of King Lear. This Lear was not published during the translator’s lifetime, Sumardjo’s prestige notwithstanding because he was not satisfied with the solutions he proposed.